(3TQM GdSjQ GdcHjQs - (3CHh HcQ eMeO Hf GHi Sgd GdSQNSis; (3eMeO GdTjHGfj , eMeO Hf GdMSf GdTjHGfj, GdTjHGfjs
(3ChdgG (B:s
(3jHOC HHGH GdYHO jYJb HESdGeg ChdG jYJb s
(3BNQgG (B:s
(3jfJgi HHGH Gdfbd ef CSdGH GdNhGQL hCgd GdMQH s
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B194s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1014s
Keywords: (3Gdabg GdMfajs